1999
DOI: 10.2337/diabetes.48.3.564
|View full text |Cite
|
Sign up to set email alerts
|

Acute vasoconstriction-induced insulin resistance in rat muscle in vivo.

Abstract: Insulin-mediated changes in blood flow are associated with altered blood flow distribution and increased capillary recruitment in skeletal muscle. Studies in perfused rat hindlimb have shown that muscle metabolism can be regulated by vasoactive agents that control blood flow distribution within the hindlimb. In the present study, the effects of a vasoconstrictive agent that has no direct effect on skeletal muscle metabolism but that alters perfusion distribution in rat hindlimb was investigated in vivo to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
114
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(123 citation statements)
references
References 29 publications
8
114
1
Order By: Relevance
“…We propose that glucosamine inhibits insulin signalling in as yet unidentified site(s), thereby blocking the increases in total flow and capillary recruitment. In so doing, impaired access for insulin and glucose may ensue, contributing to insulin resistance in a similar way to previous experimental situations, where capillary recruitment by insulin was blocked [12][13][14].…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…We propose that glucosamine inhibits insulin signalling in as yet unidentified site(s), thereby blocking the increases in total flow and capillary recruitment. In so doing, impaired access for insulin and glucose may ensue, contributing to insulin resistance in a similar way to previous experimental situations, where capillary recruitment by insulin was blocked [12][13][14].…”
Section: Discussionsupporting
confidence: 54%
“…In Table 1 Arterial and venous plasma 1-MX concentrations, femoral arterial flow rate and calculated hind limb 1-MX metabolism for anaesthetised rats infused with saline, N-glucosamine, insulin or both N-glucosamine and insulin Data were collected 180 min after the commencement of the infusions as shown in Fig. 1 Values are means±SE for n=8 in each group *p<0.05 difference from saline; # p<0.05 difference from insulin contrast, there is growing evidence that insulin-mediated capillary recruitment may play a key role in muscle glucose uptake, particularly in animal models [18] and is impaired in animal models of muscle insulin resistance [12][13][14]41] and in obese humans [42,43]. Capillary recruitment is controlled independently of limb blood flow [17,18,21] and occurs in response to locally administered physiological insulin in human forearm in association with glucose uptake [44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the rat hindlimb, insulin recruited capillary perfusion as shown by an in-crease in the metabolism of 1-methylxanthine. This capillary recruitment was related to changes in skeletal muscle glucose uptake independently of changes in total blood flow [2,3]. Furthermore, it has been shown that laser Doppler flow measurements in the constant-flow, erythrocyte-perfused rat hindlimb correlate with changes in muscle metabolism, indicating the ability of this technology to measure erythrocyte movement both proportional to nutritive flow and separate from total flow [4].…”
Section: Introductionmentioning
confidence: 97%